Towards HANK: Investigating interactions between labour and credit-market frictions in a new Keynesian economy - McKernan, M (2019)
How can the presence of unemployment affect the properties of economic fluctuations and the effectiveness of monetary policy when a fraction of households are also credit-constrained? This paper presents a New Keynesian model with limited asset market participation combined with a search & matching model of the labour market. The resulting framework uncovers a novel mechanism whereby aggregate shocks affect the hiring incentives of firms and the prevailing wage through fluctuations in the total expected surplus from an employment relationship. In the presence of credit-constraints, this will have implications for the distribution of consumption across households. Quantitative evidence suggests that these effects are indeed significant, leading to a greater volatility in labour market tightness and aggregate labour income. In response to a contraction in monetary policy, the fall in output is found to be much greater due to the interaction between credit and labour frictions, whilst the response of inflation remains quantitatively close to the baseline New Keynesian model.